Receptor tyrosine phosphatases regulate birth order-dependent axonal fasciculation and midline repulsion during development of the Drosophila mushroom body. - Kurusu, M.; Zinn, K. (Molecular and Cellular Neurosciences, 2008)
Receptor tyrosine phosphatases (RPTPs) are required for axon guidance during embryonic development in Drosophila. Here we examine the roles of four RPTPs during development of the larval mushroom body (MB). MB neurons extend axons into parallel tracts known as the peduncle and lobes. The temporal order of neuronal birth is reflected in the organization of axons within these tracts. Axons of the youngest neurons, known as core fibers, extend within a single bundle at the center, while those of older neurons fill the outer layers. RPTPs are selectively expressed on the core fibers of the MB. Ptp10D and Ptp69D regulate segregation of the young axons into a single core bundle. Ptp69D signaling is required for axonal extension beyond the peduncle. Lar and Ptp69D are necessary for the axonal branching decisions that create the lobes. Avoidance of the brain midline by extending medial lobe axons involves signaling through Lar.